Expressive illocutionary acts and politeness in managerial responses to online hotel reviews - Radovanović, Aleksandra (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper explores expressive illocutionary acts in responses to hotel guests’ reviews posted on Tripadvisor by comparing their occurrences and realizations in 320 managerial responses in English from English and Serbian hotels, with manifestations of linguistic politeness a focus of analysis. Drawing largely on Leech’s (2014) framework, the study attempts to determine whether the acts which tend to come in the form of formulaic, routinized expressions occurring in the responses given by hotels located in different cultural settings exhibit some differences as a reflection of culturespecific politeness values. The analysis has revealed considerable similarity between the two data sets in the lexicogrammatical realization of expressives and the use of resources for politeness. However, some noteworthy points of dissimilarity have emerged which correlate closely with the differences in cultural value preferences of the two countries in Hofstede et al.’s (2010) dimensions of power distance and individualism..